2019
DOI: 10.1002/mds.27614
|View full text |Cite
|
Sign up to set email alerts
|

The endocytic membrane trafficking pathway plays a major role in the risk of Parkinson's disease

Abstract: Background PD is a complex polygenic disorder. In recent years, several genes from the endocytic membrane‐trafficking pathway have been suggested to contribute to disease etiology. However, a systematic analysis of pathway‐specific genetic risk factors is yet to be performed. Objectives To comprehensively study the role of the endocytic membrane‐trafficking pathway in the risk of PD. Methods Linkage disequilibrium score regression was used to estimate PD heritability explained by 252 genes involved in the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 59 publications
(97 reference statements)
3
69
0
Order By: Relevance
“…46 As such, a significant proportion of PD-heritability is still unaccounted for, likely due to small effect sizes of undiscovered loci that do not surpass GWAS significance thresholds. 61 Here, we used polygenic risk scores to investigate the potential contribution of clathrin-trafficking genes to PD risk. Four genes were present in all PD-associated categories: AP2A1, AP2A2, SNAP91 and PICALM and two of these genes encode for isoforms of the α subunit of the AP2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…46 As such, a significant proportion of PD-heritability is still unaccounted for, likely due to small effect sizes of undiscovered loci that do not surpass GWAS significance thresholds. 61 Here, we used polygenic risk scores to investigate the potential contribution of clathrin-trafficking genes to PD risk. Four genes were present in all PD-associated categories: AP2A1, AP2A2, SNAP91 and PICALM and two of these genes encode for isoforms of the α subunit of the AP2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dominantly inherited SNCA and LRRK2 genes, a number of other genes have been linked to PD that are known to act primarily at the synapse; autosomal‐recessive mutations in PRKN , DNAJC6 , and SYNJ1 lead to juvenile onset, atypical forms of PD, and variation at the locus is a PD risk factor . (Fig.…”
Section: Genes Implicated In Pd That Play a Role At The Presynaptic Tmentioning
confidence: 99%
“…Advances in genetics and multiple model systems have revealed an important role of intracellular trafficking defects in Parkinson's disease (PD) (1)(2)(3). Importantly, a recent systematic analysis of pathway-specific genetic risk factors revealed that endocytic membranetrafficking pathway plays a major role in the risk of PD (2).…”
Section: Introductionmentioning
confidence: 99%